Legumain Regulates Differentiation Fate of Human Bone Marrow Stromal Cells and Is Altered in Postmenopausal Osteoporosis - Jafari, Abbas (Stem Cell Reports, 2017)
Secreted factors are a key component of stem cell niche and their dysregulation compromises stem cell function. Legumain is a secreted cysteine protease involved in diverse biological processes. Here, we demonstrate that legumain regulates lineage commitment of human bone marrow stromal cells and that its expression level and cellular localization are altered in postmenopausal osteoporotic patients. As shown by genetic and pharmacological manipulation, legumain inhibited osteoblast (OB) differentiation and in vivo bone formation through degradation of the bone matrix protein fibronectin. In addition, genetic ablation or pharmacological inhibition of legumain activity led to precocious OB differentiation and increased vertebral mineralization in zebrafish. Finally, we show that localized increased expression of legumain in bone marrow adipocytes was inversely correlated with adjacent trabecular bone mass in a cohort of patients with postmenopausal osteoporosis. Our data suggest that altered proteolytic activity of legumain in the bone microenvironment contributes to decreased bone mass in postmenopausal osteoporosis.